Continuity of Care in the Management of Moderate Anemia During Pregnancy: A Case Study - Rahmah Rahmah; Kamelia Sinaga; Kismiasih Adethia; Sarfina Br Sembiring; Sri Muliana Putri Bakara (Jurnal Ners, 2026)
Comments for the Editor Dear Editor, We are pleased to submit our manuscript entitled "Continuity of Care in the Management of Moderate Iron Deficiency Anemia During Pregnancy: A Case Study" for consideration for publication in Jurnal Ners. This manuscript presents a case study describing the implementation of comprehensive Continuity of Care in the management of moderate iron deficiency anemia during pregnancy. The study highlights the contribution of continuous, woman-centered midwifery care from pregnancy through childbirth, postpartum, newborn, and family planning services in improving maternal hemoglobin levels and supporting favorable maternal and neonatal outcomes. We believe that the findings provide practical insights for nurses, midwives, and other healthcare professionals involved in maternal health services. We confirm that this manuscript is original, has not been published previously, and is not under consideration for publication elsewhere. All authors have approved the final version of the manuscript and declare that there are no conflicts of interest related to this study. Thank you for your time and consideration. We appreciate the opportunity to have our manuscript evaluated for publication in Jurnal Ners. Sincerely, The Authors